Unveiling the research landscape women and Islamic Sharia in Aceh: A bibliometric review through google scholar indexed journals - Ruslan, Ruslan; Purnomo, Pungki; Mukhtaruddin, Mukhtaruddin; Nurrahmi, Nurrahmi; Ghazali, Asmadi Mohammed (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
Women have become a significant focus in the implementation of Islamic Sharia in Aceh in recent years. This paper examines the development of research on women in relation to Islamic Sharia in Aceh and maps the bibliometric relationships among articles published in Google Scholar-indexed journals from 2007 to 2023. Utilizing a quantitative method with a bibliometric approach, data was collected through a literature search using Harzing's Publish or Perish application. The analysis was conducted using the Vosviewer application, which visualizes network, overlay, and publication density aspects. The findings indicate a decline in studies on women and Islamic law by the end of 2023, with the peak publication year being 2022, which saw five articles, while only one article was published in 2023. From 2007 to 2023, a total of 22 research articles were identified, accumulating 232 citations. The most cited author during this period is Muhammad Ansor, with three articles and 93 citations. The Al-Jami'ah Journal and Analisa Journal were the leading publishers on this topic. The bibliometric relationship map revealed 163 items grouped into ten clusters, covering topics such as sharia regulations on Muslim dress, gambling, women's participation, and human rights up to 2012. In contrast, discussions from 2012 to 2022 shifted towards domestic violence, sexual violence, and protection. While subjects like sharia regulation and Muslim dress have been extensively researched, areas such as protection, human rights, and women's involvement remain underexplored.